The Role of Innovation on Economic Growth – An Overwiew of the Growth Models Including Innovation (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2014)
The main purpose of this paper is to present the concept of innovation in the context of the economic growth process. First a definition of the concept is offered together with its typology. The Schumpeterian perspective on innovation is brought in discussion, as the Austrian economist is the first notable scholar to have addressed this issue with connection to the economic growth process. The paper uses secondary data to argue the liaisons between innovation and economic growth. As the "creative destruction" comes from inside the system, being an internal factor, two endogenous growth models are analysed. The result of the study is that innovation is correlated with economic growth, the volume of research activities and their results influencing the level of economical advancement.